Chronic hepatitis delta virus infection in Van region of eastern Turkey - M. Kürşat TÜRKDOĞAN; Hamza BOZKURT; İsmail UYGAN; İlyas TUNCER; Hasan IRMAK; Turan BUZGAN; Hayrettin AKDENİZ (Turkish Journal of Gastroenterology, 2019)
-